2016
DOI: 10.1186/s12906-016-1031-2
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol extract of Pinus koraiensis leaves containing lambertianic acid exerts anti-obesity and hypolipidemic effects by activating adenosine monophosphate-activated protein kinase (AMPK)

Abstract: BackgroundIn this study, we investigated the anti-obesity and anti-hyperlipidemic mechanisms of lambertianic acid (LA) isolated from Pinus koraiensis leaves and the ethanol extract of Pinus koraiensis leaves (EPK), both in vitro and in vivo.MethodsDifferentiated 3T3L-1 cells were treated with EPK (25 or 50 μg/mL) or LA (200 μM) and analyzed by western blotting or RT-PCR. In vitro, lipid accumulation of adipocytes was observed using Oil-Red-O staining and triglyceride analysis. The contribution of AMPK to anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 43 publications
2
21
0
Order By: Relevance
“…thus, The utilization of AMPK or perhaps the regulation of downstream targets may provide potential therapeutic targets in the treatment of prostate cancer41. Of note, in line with our results, the compound C directly inhibition of the phosphorylation of AMPK itself have been reported in several other studies424344. Concerning an additional feedback role, the effects of compound C on AMPK signaling could be more complicated then we thought.…”
Section: Discussionsupporting
confidence: 86%
“…thus, The utilization of AMPK or perhaps the regulation of downstream targets may provide potential therapeutic targets in the treatment of prostate cancer41. Of note, in line with our results, the compound C directly inhibition of the phosphorylation of AMPK itself have been reported in several other studies424344. Concerning an additional feedback role, the effects of compound C on AMPK signaling could be more complicated then we thought.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, lambertianic acid (LA), a natural compound from Pinus koraiensis , was known to suppress obesity in 3T3‐L1 cells (Lee et al, ) and induce apoptosis in hepatocellular carcinoma cancer cells (Jeong, Kim, Lee, & Kim, ). Nevertheless, the underlying mechanisms of LA in breast cancer cells still remain unclear to date.…”
Section: Introductionmentioning
confidence: 99%
“…LA is found to naturally occur in Pinaceae or Cupressaceae family species [ 20 , 21 ]. We recently reported that LA, a bioactive constituent of P. koraiensis , has anti-obesity effects [ 22 ]. Nevertheless, the specific effect of LA on tumor proliferation and survival has not been examined previously.…”
Section: Discussionmentioning
confidence: 99%